Systematic review on the neurological impacts of congenital Zika Virus infection: Pathophysiological mechanisms and clinical implications (Research, Society and Development, 2025)
Congenital Zika virus (ZIKV) infection is intrinsically linked to severe neurological impairments in newborns, with significant repercussions on child development. This systematic review, based on observational and experimental studies (2015-2024), investigated the pathophysiological mechanisms and clinical implications of this condition. The results demonstrate that ZIKV preferentially infects neural progenitor cells (NPCs) by interacting with receptors (AXL, TAM, DC-SIGN), triggering apoptosis, TLR3-mediated inflammation, and disruption of neurogenesis. These processes result in malformations such as microcephaly (present in 96% of cases), intracranial calcifications (93%), ventriculomegaly (78%), and dysgenesis of the corpus callosum, identifiable by imaging techniques (CT/MRI). A longitudinal analysis revealed long-term consequences: 31.5% of children presented neuropsychomotor delays at 18 months, with motor, cognitive, and sensory deficits (hearing/visual loss in 30%), as well as refractory epilepsy and arthrogryposis. Promising strategies include vector control with Wolbachia, vaccines (ZPIV, mRNA) under development, and antivirals such as sofosbuvir, which reduced viral replication in experimental models. The conclusion is that the integration of early imaging, neuroprotective therapies, and multidisciplinary approaches is crucial to mitigating neurological damage, reinforcing the need for public policies focused on epidemiological surveillance and early rehabilitation.